Nurse practitioner and physician assistant scope of practice in 118 acute care hospitals - Anand Kartha; Joseph D. Restuccia; James Burgess; Justin K. Benzer; Justin Glasgow; Jason M. Hockenberry; David C. Mohr; Peter J. Kaboli (2014)
BACKGROUND Advanced practice providers (APPs), including nurse practitioners (NPs) and physician assistants (PAs) are cost‐effective substitutes for physicians, with similar outcomes in primary care and surgery. However, little is understood about APP roles in inpatient medicine. OBJECTIVE Describe APPs role in inpatient medicine. DESIGN Observational cross‐sectional cohort study. SETTING One hundred twenty‐four Veterans Health Administration (VHA) hospitals. PARTICIPANTS Chiefs of medicine (COMs) and nurse managers. MEASUREMENTS Surveys included inpatient medicine scope of practice for APPs and perceived healthcare quality. We conducted bivariate unadjusted and multivariable adjusted analyses. RESULTS One hundred eighteen COMs (95.2%) and 198 nurse managers (75.0%) completed surveys. Of 118 medicine services, 56 (47.5%) employed APPs; 27 (48.2%) used NPs only, 15 (26.8%) PAs only, and 14 (25.0%) used both. Full‐time equivalents for NPs was 0.5 to 7 (mean = 2.22) and PAs was 1 to 9 (mean = 2.23). Daily caseload was similar at 4 to 10 patients (mean = 6.5 patients). There were few significant differences between tasks. The presence of APPs was not associated with patient or nurse manager satisfaction. Presence of NPs was associated with greater overall inpatient and discharge coordination ratings by COMs and nurse managers, respectively; the presence of PAs was associated with lower overall inpatient coordination ratings by nurse managers. CONCLUSIONS NPs and PAs work on half of VHA inpatient medicine services with broad, yet similar, scopes of practice. There were few differences between their roles and perceptions of care. Given their very different background, regulation, and reimbursement, this has implications for inpatient medicine services that plan to hire NPs or PAs. Journal of Hospital Medicine 2014;9:615–620. © 2014 Society of Hospital Medicine